2008
DOI: 10.14778/1453856.1453924
|View full text |Cite
|
Sign up to set email alerts
|

Main-memory scan sharing for multi-core CPUs

Abstract: Computer architectures are increasingly based on multi-core CPUs and large memories. Memory bandwidth, which has not kept pace with the increasing number of cores, has become the primary processing bottleneck, replacing disk I/O as the limiting factor. To address this challenge, we provide novel algorithms for increasing the throughput of Business Intelligence (BI) queries, as well as for ensuring fairness and avoiding starvation among a concurrent set of such queries. To maximize throughput, we propose a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…There may be opportunities to optimize this final stage, e.g., by sharing work among aggregation operators, depending on the current query mix. This optimization is orthogonal to Cjoin and can employ existing techniques [10,24].…”
Section: The Distributormentioning
confidence: 99%
See 2 more Smart Citations
“…There may be opportunities to optimize this final stage, e.g., by sharing work among aggregation operators, depending on the current query mix. This optimization is orthogonal to Cjoin and can employ existing techniques [10,24].…”
Section: The Distributormentioning
confidence: 99%
“…Cooperative scans [31] improve data sharing across concurrent scans by dynamically scheduling queries and their data requests, taking into account current system conditions. Qiao et al [24] have investigated shared memory scans as a specific form of work sharing in multi-core systems: by scheduling concurrent queries carefully, tuple accesses can be coordinated in the processor's cache. Another possibility is to recycle intermediate results and share them with subsequent queries [17].…”
Section: Work Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Shared scans have been implemented in the context of disk-based systems such as Red Brick DW [34], DB2 UDB [57], and MonetDB/X100 [79]. Shortly before Crescando, Raman et al [63,64] had demonstrated that shared scans in main memory can provide predictable, low ("constant") access latency.…”
Section: Scan-only Query Processingmentioning
confidence: 99%
“…Circular scans are implemented in a variety of systems [7,8,9,14] and they can sustain a large number of concurrent tablescans by reducing contention for the buffer pool and the number of accesses to the underlying storage devices. More elaborate techniques for shared scans with coordination are developed for column-stores [29] and for main-memory shared scans [21].…”
Section: Related Workmentioning
confidence: 99%